2016
DOI: 10.1097/pas.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Fumarate Hydratase–deficient Renal Cell Carcinoma Is Strongly Correlated With Fumarate Hydratase Mutation and Hereditary Leiomyomatosis and Renal Cell Carcinoma Syndrome

Abstract: Hereditary leiomyomatosis and renal cell carcinoma syndrome-associated renal cell carcinomas (RCC) are difficult to diagnose prospectively. We used immunohistochemistry (IHC) to identify fumarate hydratase (FH)-deficient tumors (defined as FH negative, 2-succinocysteine [2SC] positive) in cases diagnosed as "unclassified RCC, high grade or with papillary pattern," or "papillary RCC type 2," from multiple institutions. A total of 124 tumors (from 118 patients) were evaluated by IHC for FH and 2SC. An FH deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
260
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 203 publications
(272 citation statements)
references
References 25 publications
(31 reference statements)
6
260
1
5
Order By: Relevance
“…Cells share a characteristic appearance; a large nucleus and prominent inclusion-like eosinophilic nucleoli surrounded by a clear halo [12]. Immunohistochemistry demonstrates a lack of FH protein expression and increased 2SC levels in the tumor [1315]; a finding that should prompt genetic screening of affected individuals. Traditionally ‘type 2 papillary RCCs’ were the renal lesion most commonly associated with HLRCC, however a recent genomic analysis has suggested that ‘type 2 papillary RCC’ is not in fact a single tumor type, but instead consists of sub-groups with different molecular backgrounds [16].…”
Section: Discussionmentioning
confidence: 99%
“…Cells share a characteristic appearance; a large nucleus and prominent inclusion-like eosinophilic nucleoli surrounded by a clear halo [12]. Immunohistochemistry demonstrates a lack of FH protein expression and increased 2SC levels in the tumor [1315]; a finding that should prompt genetic screening of affected individuals. Traditionally ‘type 2 papillary RCCs’ were the renal lesion most commonly associated with HLRCC, however a recent genomic analysis has suggested that ‘type 2 papillary RCC’ is not in fact a single tumor type, but instead consists of sub-groups with different molecular backgrounds [16].…”
Section: Discussionmentioning
confidence: 99%
“…The second cohort of cases studied is composed of two published, well characterized cohorts of cases with FH-deficient status (n=23) (18) or HLRCC-RCC (n=9) (14). These previously reported cases were reviewed to determine whether any TC-PD morphology were apparent, at least focally.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, HLRCC-RCCs are exceptionally aggressive tumors, often presenting at high stage, underscoring the importance of their recognition (12, 14). Thus recent reports propose immunohistochemical adjuncts for screening for HLRCC-RCCs, including staining for FH protein expression, which may be lost in a majority of cases (15-18) and for aberrant succination of nuclear and cytoplasmic proteins (S-(2-succino)-cysteine, 2SC), which is induced upon loss of FH function (14, 17, 19, 20). …”
Section: Introductionmentioning
confidence: 99%
“…46 Recently, immunohistochemistry for FH and S-(2-succino)cysteine have been shown to be useful for detecting HLRCC-associated RCCs. [51][52][53] In these tumors, loss of heterozygosity at the FH locus results in loss of cytoplasmic FH protein expression in most cases ( Figure 2, D); in addition, loss of the FH protein function leads to accumulation of aberrantly succinated proteins, which can be detected as increased cytoplasmic/nuclear S-(2-succinyl)cysteine expression. 54 Together, these 2 immunostains have a high sensitivity and specificity for detecting HLRCC-associated RCCs.…”
Section: Rcc With Papillary Architecturementioning
confidence: 99%
“…54 Together, these 2 immunostains have a high sensitivity and specificity for detecting HLRCC-associated RCCs. 51,52 In general, HLRCC-associated RCC has an aggressive clinical course, with frequent metastasis and subsequent death. 48 As such, the identification of patients with HLRCC-associated RCC is important because these patients (and their families) should undergo genetic evaluation and counseling.…”
Section: Rcc With Papillary Architecturementioning
confidence: 99%